Balkan genocides : holocaust and ethnic cleansing in the twentieth century - Mojzes, Paul 1936- (Studies in genocide : religion, history, and human rights, 2011)
Details the history of the three major waves of genocide and ethnic cleansing in the Balkan peninsula and Yugoslavia during the twentieth century